Rapid communications in mass spectrometry : RCM (John Wiley & Sons, 1987)
Abstracts and full-text, 1997- ; abstracts only, 1996.
Keywords: Mass spectrometry : Periodicals; Mass Spectrometry; Spectrométrie de masse : Périodiques; Spectrométrie de masse; mass spectrometry; Mass spectrometry